2008
DOI: 10.1007/s10534-008-9137-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ascorbate-mediated iron release from ferric phytosiderophores in the presence of nicotianamine

Abstract: Phytosiderophores (PS) are strong iron chelators, produced by graminaceous plants under iron deficiency. The ability of released PS to chelate iron(III), and subsequent uptake of this chelate into roots by YS1-type transport proteins, are well-known. The mechanism of iron release from the stable chelate inside the plant cell, however, is unclear. One possibility involves the reduction of ferric PS in the presence of an iron(II) chelator via ternary complex formation. Here, the conversion of ferric PS species b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Related observations were reported by Weber et al, investigating the potential role of the reductive mechanism in the siderophore mediated uptake of iron in various plants (Weber et al 2008). Two iron uptake strategies have been observed to be operative in plants; strategy I involves reduction of the metal center by biological reductants at the plasma membrane of the root cell, followed by hydrolysis of the complex by increased secretion of protons and uptake of the iron(II); strategy II, observed primarily in grasses, involves uptake of the entire iron-siderophore complex by receptors on the root cell surface, followed by reduction within the root cell (Schmidt 2003).…”
Section: Shifting Iron-siderophore Complex Redox Potentialssupporting
confidence: 74%
See 1 more Smart Citation
“…Related observations were reported by Weber et al, investigating the potential role of the reductive mechanism in the siderophore mediated uptake of iron in various plants (Weber et al 2008). Two iron uptake strategies have been observed to be operative in plants; strategy I involves reduction of the metal center by biological reductants at the plasma membrane of the root cell, followed by hydrolysis of the complex by increased secretion of protons and uptake of the iron(II); strategy II, observed primarily in grasses, involves uptake of the entire iron-siderophore complex by receptors on the root cell surface, followed by reduction within the root cell (Schmidt 2003).…”
Section: Shifting Iron-siderophore Complex Redox Potentialssupporting
confidence: 74%
“…1). However, it was shown that iron could be removed from PS by nicotinamine in the presence of ascorbic acid (Weber et al 2008). Weber et al proposed a mechanism involving formation of a ternary complex between the iron(III)-PS complex and the biological reducing agent ascorbic acid that resulted in reduction of the metal center, followed by exchange of the ascorbate oxidation product with nicotinamine, leading to final formation of the iron(II)-nicotinamine complex.…”
Section: Shifting Iron-siderophore Complex Redox Potentialsmentioning
confidence: 99%
“…NA plays a key role in iron homeostasis by ensuring iron solubility in the weakly alkaline environment of the plant cytoplasm (Douchkov et al, 2005;Weber et al, 2008). Plants lacking NA (such as the tomato [Solanum lycopersicum] mutant chloronerva) show phenotypes of interveinal chlorosis in young tissues (Cassin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Kannan (1971) reported the presence of a carrier for Fe 2+ uptake in rice plants; recently, OsNRAMP1 and AtNRAMP1 (Curie et al 2000) were reported to be divalent metal transporters, localized at plasma membranes and function to take up Fe In root cells, iron may be symplasmically transported in the forms of Fe-NA, Fe-citrate and Fe-PSs to the xylem. To use iron for root metabolism, the ferric iron of Fe(III)-citrate, if present, can be reduced to ferrous by NADH-nitrate reductase (Redinbangh and Campbell 1983), and the ferric iron of Fe(III)-PSs can be reduced to ferrous form by ascorbate, forming Fe(II)-NA (Weber et al 2008).…”
Section: Fe-chelate Complexes In Xylem Sapmentioning
confidence: 99%